Population Of Worm Soil Preparation On Land And Management Of Weeds Three District In North Sumatra Province - Fitria Fitria (JASc (Journal of Agribusiness Sciences), 2018)
This research is to know the level of population of tanag worms with some ways of land preparation and weed management in Deli Serdang, Karo, Simalungun Regency. This research was conducted in three places, namely Deli Serdang, Karo and Simalungun District of North Sumatera Province, from July to September 2013. The observation of earthworms was done by quadratic and Hand Sortir method, plot plots were made with frame measuring 30 x 30 cm, soil sampling as deep as 20 cm in each frame then put into container. Sampling starts from 7:00 to 10:00 pm then land is sorted to get earthworms. Earthworms that can be collected and cleaned are then counted and then put into a bottle sample container and preserved with 70% alcohol then the underground worm sample below to the Systematic Laboratory of FMIPA USU to be identified and counted the number of individuals of each species found (Sumi, 1997). The soil worms that have been preserved by using 70% alcohol are first grouped according to their species then determined and identified by morphology using a microscope. Data analysis The type of earthworm and the number of individuals of each type obtained were calculated Population density, Relative density of each type of Attendance and Composition Frequency. The results of the research and identification done on land preparation and weed management on the land in Simalungun, Deli Serdang and Karo regencies are found in the Simalungun Regency there are 2 families: Glossoscoleadae (species Pontoscolex and Megascolex) and Megascolecidae (Megascolex species). In Kabupaten Deli Serdang there is one family Megascolecidae (species Megascolex) and Karo there is 1 family Megascolecidae (species Peryonix)